THE STUDY OF PHYSIOLOGICAL PECULIARITIES OF FUNCTIONAL ACTIVITY OF FEMALE PLAYER’S BODY WHILE PLAYING MINI-FOOTBALL - Shapoval, Ye.Yu.; Momot, O.O.; Sviertniev, O.A.; Khomenko, P.V. (World of Medicine and Biology, 2018)
In order to achieve the maximum efficiency of playing activities in women's teams in mini-football, it is necessary to strictly plan the training process, taking into account the specifics and features of the female body. During the training process, cases occur when physiological peculiarities of the female body’s functional activity are neglected, though they have certain differences in comparison to the male ones. On the basis of the performed research studies analysis, the author considers approaches to the physical activity load differentiation and focusing the training process of soccer players, which takes into account the peculiarities of the of the female body’s activity in each phase of the ovarian menstrual cycle (OMC).Despite the active participation of women in such a popular sport as football, studies clarifying the peculiarities of soccer players' activity during OMC are insufficient in number. One of the features in the current sports is wide involvement of women participating in the vast majority of its types. At the same time, in training women athletes, their gender differences are often ignored and a women's training is carried out according to the techniques developed for men in the similar sports. This is particularly true for those sports that were traditionally considered to be "male" ones, and now they are experiencing a period of rapid development as those of "female".The problem of approaches to training women in such sports as mini-soccer requires a comprehensive, detailed study and scientific substantiation. The author carried out a theoretical analysis of the problem under study. It has been determined that a differentiated approach is the trainer’s implementation of drilling and training tasks according to the age, gender, level of training status in athletes. A differentiated approach in the training process lies initially in the disclosure of the athlete individuality, and then in the selection of the most favorable conditions for development through the suggested differentiated teaching and training methods. A scheme for implementing the multiple-factor differentiation of the training process in mini-football was developed.We consider that the most informative indicators of the motion skills formation in women's mini-football in the preparatory period at the stages of preliminary and specialized basic training, are the technical indicators, therefore the correlation between the gnosiological and technical indicators has been calculated. The technical index was obtained as a result of measuring the number of ultimate hits on the gate (with a forefoot, ball of the foot, inner side of the foot) and ball dribbling.When planning the training process for the girls engaged in mini-football the trainer must take into account the functional capabilities of the female body (in particular, OMC), the specifics of women's mini-football, the conditions of training the football players, the laws of improving various qualities, etc.
Keywords: mini-football; training process; physiological characteristics; female organism; volume of loads; differentiation